2022
DOI: 10.1038/s41557-022-00950-z
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning study of tyrosine reveals that roaming can lead to photodamage

Abstract: How to cite:Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 65 publications
1
30
0
1
Order By: Relevance
“…The correlation between the photodegradation kinetics-based dFe speciation and phytoplankton uptake-based dFe bioavailability is used for the test of the BDIS validation. Density functional theory (DFT) is a quantum chemical method 29 for studying the electronic structure of molecules. Based on DFT, the geometry optimization and chemical description for the molecular structures of 12 species of Fe−organic ligands (1:1) are performed; using the Gaussian09 program 30 package with B3LYP exchange−correlation functional and 6-311+G** basis set, the configurational formation energy (CFE) of dFe complexes is calculated.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The correlation between the photodegradation kinetics-based dFe speciation and phytoplankton uptake-based dFe bioavailability is used for the test of the BDIS validation. Density functional theory (DFT) is a quantum chemical method 29 for studying the electronic structure of molecules. Based on DFT, the geometry optimization and chemical description for the molecular structures of 12 species of Fe−organic ligands (1:1) are performed; using the Gaussian09 program 30 package with B3LYP exchange−correlation functional and 6-311+G** basis set, the configurational formation energy (CFE) of dFe complexes is calculated.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Marquetand and coworkers applied the SchNarc approach to investigate the photodissociation reaction of tyrosine that shows a dissociation channel of a hydrogen radical with a chemically non-intuitive path which is called roaming. 201 Roaming was originally explored experimentally and computationally in formaldehyde by Bowman and coworkers in 2004 but real-time experimental observation were not achieved until 2020. 202,203 The NNP is learned to reproduce 29 energy values and force values for electronic singlet and triplet states and 812 spin-orbit couplings.…”
Section: Reaction Ratesmentioning
confidence: 99%
“…The use of CASSCF data must be carefully validated against multireference methods, such as multireference configuration interaction (MRCI) and extended multistate complete active space second-order perturbation theory (XMS-CASPT2). We recommend the ANO-type double-ζ basis set or comparable aug-cc-pVDZ basis set because they provide a balance between computational cost and accuracy and capture diverse excitation types, including Rydberg states. , Moreover, Bowan, Lester, and co-workers showed that in the dissociation of CH 3 COO Criegee intermediates and more recently Marquet and and co-workers showed that in the dissociation of tyrosine, there are no available reference methods can describe the entire reaction space, requiring a combination of QC methods to be employed.…”
Section: The ML Photodynamics Approachmentioning
confidence: 99%